The germinal center kinase TNIK is required for canonical NF-κB and JNK signaling in B-cells by the EBV oncoprotein LMP1 and the CD40 receptor. - Anna Shkoda (Public Library of Science (PLoS), 2012)
The tumor necrosis factor-receptor-associated factor 2 (TRAF2)- and Nck-interacting kinase (TNIK) is a ubiquitously expressed member of the germinal center kinase family. The TNIK functions in hematopoietic cells and the role of TNIK-TRAF interaction remain largely unknown. By functional proteomics we identified TNIK as interaction partner of the latent membrane protein 1 (LMP1) signalosome in primary human B-cells infected with the Epstein-Barr tumor virus (EBV). RNAi-mediated knockdown proved a critical role for TNIK in canonical NF-κB and c-Jun N-terminal kinase (JNK) activation by the major EBV oncoprotein LMP1 and its cellular counterpart, the B-cell co-stimulatory receptor CD40. Accordingly, TNIK is mandatory for proliferation and survival of EBV-transformed B-cells. TNIK forms an activation-induced complex with the critical signaling mediators TRAF6, TAK1/TAB2, and IKKβ, and mediates signalosome formation at LMP1. TNIK directly binds TRAF6, which bridges TNIK's interaction with the C-terminus of LMP1. Separate TNIK domains are involved in NF-κB and JNK signaling, the N-terminal TNIK kinase domain being essential for IKKβ/NF-κB and the C-terminus for JNK activation. We therefore suggest that TNIK orchestrates the bifurcation of both pathways at the level of the TRAF6-TAK1/TAB2-IKK complex. Our data establish TNIK as a novel key player in TRAF6-dependent JNK and NF-κB signaling and a transducer of activating and transforming signals in human B-cells.